Program Penguatan Resiliensi dan Manajemen Stres bagi Pekerja Pariwisata di Kawasan Sanur Denpasar - I Made Andika Naraditha; I Wayan Adis Hordinata; I Made Augie Putra Budiartha; Ida Bagus Ary Indra Dhuaja (Jurnal PKM Manajemen Bisnis, 2026)
This community service activity was motivated by the high level of work-related stress experienced by tourism workers in the Sanur area of Denpasar, resulting from excessive workloads, post-pandemic economic uncertainty, and limited psychosocial support. These conditions have contributed to decreased motivation and work performance. The partner-related problems identified included low levels of understanding of stress management and the absence of systematic strategies to strengthen worker resilience. The objective of this program was to enhance mental health literacy, improve stress management skills, and foster a more adaptive and supportive work culture among tourism workers. The activity was conducted in Sanur, Denpasar, in July 2025. Participants consisted of 34 tourism workers, while the implementation team comprised five lecturers and students from Universitas Pendidikan Nasional. The program employed participatory training methods, group discussions, relaxation and mindfulness practice sessions, as well as pre-test and post-test assessments. The results demonstrated an increase in participants’ knowledge of stress management, improved coping skills, more positive attitudes toward stress, and enhanced work motivation. Evaluation findings also indicated improved social interaction among participants and increased institutional support to sustain the program. In conclusion, this structured yet simple intervention effectively addressed the partners’ needs, and it is recommended that future initiatives include advanced training and the establishment of workplace support groups to ensure long-term impact and sustainability.